COMMUNITY EMPOWERMENT MODEL IN TELUK PANGPANG AREA, BANYUWANGI BASED ON MANGROVE FOREST MANAGEMENT BASED ON STUDY OF PENTAGON ASSET - Zainal, Zainal Abidin; Iqbal, Iqbal; Nurtania, Nurtania Sudarmi (Nusantara Journal Of Management Business (NUMABI), 2025)
This study explores a community empowerment model in the Teluk Pangpang area, Banyuwangi, using the Pentagon Asset approach, focused on mangrove management. The Pentagon Asset encompasses five key elements: human, natural, physical, financial, and social assets, which are analyzed in-depth to identify the potential and challenges in improving the welfare of coastal communities. Teluk Pangpang, with its rich and diverse mangrove ecosystem, offers significant economic opportunities through the development of ecotourism, silvofishery, and other conservation practices. This research formulates an adaptive and contextual empowerment model that integrates environmental conservation with local economic development. The study's findings indicate that optimizing the pentagon assets can enhance community participation, strengthen social networks, and create sustainable mangrove management mechanisms. These findings provide valuable insights for the development of effective natural resource management strategies while supporting economic improvement for coastal communities in Teluk Pangpang and similar regions.